Game-Based Learning Utilised Kahoot! Application for Mathematics Literacy and Motivation Among Primary Students: Experimental Study - Yanuarto, Wanda Nugroho; Hanum, Latifah (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
This study explores how game-based learning using the Kahoot! application can enhance mathematics literacy and learning motivation among primary school students. Employing a quantitative experimental approach, the research involved two student groups: the experimental group engaged in math lessons incorporating Kahoot!, while the control group received conventional teacher-centered instruction. A total of sixty elementary students took part in the study. To evaluate outcomes, mathematics literacy was assessed through pre-tests and post-tests, while a motivation questionnaire gauged students' engagement and attitudes toward learning math. The findings showed that the experimental group experienced significantly greater gains in both mathematics literacy and motivation. The interactive, game-like nature of Kahoot! created a more enjoyable and participatory learning atmosphere, promoting better understanding of mathematical concepts. These results indicate that game-based learning tools like Kahoot! can enhance academic performance and foster a more positive attitude toward mathematics. The study underscores the potential of digital learning innovations to make classrooms more interactive and student-focused, ultimately supporting the development of key mathematical skills in primary education.